The Skull of Phyllomedusa sauvagii (Anura, Hylidae) - Ruiz Monachesi, Mario Ricardo (2016)
The hylid genus Phyllomedusa comprises charismatic frogs commonly known as monkey, leaf or green frogs, and is the most diverse genus of the subfamily Phyllomedusinae, including about 31 species. Although there is some information about the anatomy of these frogs, little is known about the osteology. Here the adult skull of Phyllomedusa sauvagii, both articulated and disarticulated, is described and the intraspecific variation is reported. Additionally, cartilage associated with the adult skull, such as the nasal capsules, auditory apparatus, and hyobranchial apparatus, are included in the analysis. Further examination of disarticulated bones reveals their remarkable complexity, specifically in the sphenethmoid and of the oocipital region. The description of disarticulated bones is useful for the identification of fossil remains as well as providing morphological characteristics that are phylogenetically informative. When comparing the skull morphology with the available information of other species of the genus, Phyllomesusa sauvagii skull resembles more that of P. vaillantii and P. venusta than P. atelopoides. Anat Rec, 299:557-572, 2016.